Personalized total neoadjuvant therapy (pTNT) for advanced rectal cancer with tailored treatment sequencing based on clinical stage at presentation. Issue 1 (4th September 2022) - Bedrikovetski, Sergei; Fitzsimmons, Tracy; Perry, Joanne; Vather, Ryash; Carruthers, Scott; Selva‐Nayagam, Sudarsha; Thomas, Michelle L.; Moore, James W.; Sammour, Tarik
Abstract: Background: This study aimed to assess short‐term outcomes of a personalized total neoadjuvant treatment (pTNT) protocol, with treatment sequencing based on clinical stage at presentation. Methods: A multidisciplinary pTNT protocol was implemented across two metropolitan hospitals. This consists of two‐schema based on clinical stage: patients with distant failure risk were offered induction chemotherapy before chemoradiation (nCRT), and patients with locoregional failure risk received nCRT followed by consolidation chemotherapy. Patients underwent surgical resection unless a complete clinical response (cCR) was achieved, in which case non‐operative management (NOM) was offered. A prospective cohort analysis of all patients with rectal cancer who underwent pTNT with curative intent between Jan 2019 and Aug 2022 was performed. Results: Of 270 patients referred with rectal cancer, 102 received pTNT with curative intent and 79 have completed their treatment thus far. Thirty‐three patients (41.8%) received induction chemotherapy and 46 (58.2%) received consolidation chemotherapy per protocol. The percentage of patients with EMVI, resectable M1 disease, cT4 disease, and positive lateral lymph nodes were 54.4%, 36.7%, 27.8% and 15.2%, respectively. Overall, 32 (40.5%) patients had cCR and 4 (5.1%) pCR, and 40 (50.6%) patients had non‐operative management. Grade 3 toxicity was reported in 10.1% of patients and only three patients (3.8%) experienced Grade 4 chemotherapy‐related toxicity, with no treatment related mortality. Conclusion: Early results with a defined two‐schema pTNT protocol are encouraging and suggest that tailoring sequencing to disease risk at presentation may represent the optimal balance between local and distant disease control, as well as treatment toxicity. Abstract : Total neoadjuvant therapy for advanced rectal cancer is rapidly gaining adoption but optimal sequencing of chemotherapy and radiotherapy remains uncertain. We assess short term outcomes of a personalised total neoadjuvant treatment protocol, with treatment sequencing based on clinical stage at presentation.